Evaluation of Different Barley Genotypes for their Phenological Traits, Yield and Yield Attributes in the Western Mid-Hill of Nepal - Acharya, R.; Adhikari, B.; Bharati, S.; Paudel, H.; Subedi, S.; Acharya, B. (Journal of Agriculture and Environment, 2021)
There is a need to increase the yield potential of barley by utilizing improved cultivars. So, the present study was done to assess the performance of barley genotypes for phenological and yield attributing traits. A field study was carried out at Lumle, Kaski in Nepal involving seven barley genotypes during two growing seasons in 2018/2019 and 2019/2020, employing RCB design replicated three times. The results, combined for the years, showed significant differences for all traits except effective tillers/m2 and thousand grains weight. The grain yield was highest for B86122-1-0K-3 (2.756 t/ha and was at par with the genotypes Xveola-28 (2.411 t/ha) and B90K-024-1-1-2-0K (2.350 t/ha) and significantly higher than the Bonus (standard check) (1.852 t/ha). These superior genotypes should be further evaluated at on-station and on-farm conditions of western hills of Nepal so that low and stagnating barley yield in Nepal can be improved